1980
DOI: 10.1007/bf03349373
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity of ACTH and corticosterone in the rat

Abstract: The circadian secretion of ACTH and corticosterone was assessed by measuring immunoreactive ACTH concentration in the plasma and ACTH content in the anterior and posterior pituitary over a 30 h period in groups of both male and female rats and comparing these data to fluorometric corticosterone concentration in the plasma and corticosterone content in the adrenal. A circadian rhythm of plasma corticosterone levels and adrenal content was apparent in both males and females with the highest levels at the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…Because changes in plasma corticosterone in response to acute stress are known to occur relatively slowly (over a period of minutes) (9,28,29) compared with more immediate I-ACTH changes, these results indicate that differences observed between the chronically cannulated and the decapitated rats reflect the stress associated with sampling. A similar effect of sampling stress may also explain why Allen-Rowlands et al (5) were able to show clear diurnal variation in plasma corticosterone, but not in plasma I-ACTH, in decapitated male and female rats.…”
Section: Discussionmentioning
confidence: 78%
“…Because changes in plasma corticosterone in response to acute stress are known to occur relatively slowly (over a period of minutes) (9,28,29) compared with more immediate I-ACTH changes, these results indicate that differences observed between the chronically cannulated and the decapitated rats reflect the stress associated with sampling. A similar effect of sampling stress may also explain why Allen-Rowlands et al (5) were able to show clear diurnal variation in plasma corticosterone, but not in plasma I-ACTH, in decapitated male and female rats.…”
Section: Discussionmentioning
confidence: 78%
“…2b). The CORT response was significantly higher in the OVX group compared to the steroid replacement groups at every time point poststress except at 60 min (overall treatment: F = 5.12 [2,15]; p = 0.02; treatment and time interaction: F = 4.41; p = 0.0007). Again, the initial rate rise of CORT was significantly (p < 0.05) higher in the OVX group (31.1 ng/ml x min) compared to the group with E2 pellets (21.5 ng/ml x min) or the group with both E2 and P pellets (13.7 ng/ml x min).…”
Section: Fast Feedback Inhibition By Rising Levels O F Co Rt On a Submentioning
confidence: 87%
“…ACTH levels were ele vated in the ovariectomized group even at 20 min after the onset of the initial stress, while by this time ACTH levels were no longer different from basals in the other two groups. There was an overall treatment effect (F = 16.87 [2,15];p = 0.0001), a highly significant time effect, and a time and treatment interaction (F = 5.00; p = 0.003). Post hoc comparisons revealed that the OVX+E: and the OVX+Ei+P groups did not differ from each oth er, but were different from OVX at every time point poststress except at 60 min.…”
Section: Fast Feedback Inhibition By Rising Levels O F Co Rt On a Submentioning
confidence: 91%
See 1 more Smart Citation
“…see ref . 18] and that it is involved not only in the control of the ACTH/corticosterone response to stress or to insulin administration [19,20], but also in regulation of the ACTH/corticosterone rise during the morning hours [21,22], Corticosteroids and ACTH have a diurnal rhythm with a nadir in the light period and peak secretion during the dark period [23]. Studies of Bellomo et al [24] have shown lower 24-hour integrated concentra tions of ACTH/cortisol in parkinsonian patients as com pared with normal controls and have suggested that a hypothalamic disturbance is responsible for this disorder.…”
Section: Discussionmentioning
confidence: 99%